Effects of Heavy Metal Pollution on the Element Distribution in Hydrobios - Hu, Chengxin; Lai, Chenghao; Yu, Ruiyang; Chen, Yangfan; Shen, Zhixiao; Lu, Wei; Yuan, Xiaofeng (Toxics (Basel), 2024)
At a time when heavy metal pollution is increasing, assessing the levels of contamination and associated health risks is crucial. Samples of water, aquatic plants, and fish were collected from four key areas of heavy metal pollution prevention and control in Zhejiang Province. The levels of elements were analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES). A human health risk model was also developed. The study revealed that heavy metal pollution in the five industrial zones exceeded the national standard for Class V water. Elements like arsenic (As), cadmium (Cd), and chromium (Cr) exceeded permissible levels in aquatic plants across all industrial zones; the exception was lead (Pb). Moreover, the heavy metal concentrations in subject fish tissues collected from each industrial area exceeded safe limits, especially in the gut. According to the human health risk evaluation model, the health risk (1.12 × 10−3) and children’s health risk (1.10 × 10−3) in these prevention and control zones surpassed the maximum acceptable human risk values. In conclusion, heavy metal elements, along with other pollutants, accumulate and become concentrated in the examined aquatic plants and fish. These pollutants move through the food chain, impacting the entire aquatic ecosystem and posing a health risk to nearby populations.